Strengthening Character Education: Strategies of Elementary Teachers in Fostering Nationalism and Patriotism among Elementary School Students - Khasanah, Uswatun; Lestari, Intan (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: Indonesia is currently facing challenges in the realm of character education, particularly concerning the declining sense of nationalism and patriotism among students. These values are fundamental in shaping responsible citizens who are committed to their nation’s unity and development. Strengthening such character traits from an early age, especially at the elementary level, is crucial. Objective: This study aims to explore the strategies employed by teachers at SDIT Al-Qiswah, Bengkulu City, in fostering and strengthening the character values of nationalism and love for the country among elementary school students. Method: This research uses a qualitative field study approach. Data were collected through primary and secondary sources using observation, interviews, and documentation methods. The validity of data was tested using triangulation of sources and techniques, while the data analysis was conducted using an interactive model. Result: The findings indicate that teachers implement several strategies to strengthen students’ nationalism and patriotism. These include role modeling, habituation, storytelling, discussions, school programs, the use of learning media, the application of rewards and punishments, and collaboration between teachers and students' parents. Conclusion: Teachers at SDIT Al-Qiswah effectively apply a variety of character education strategies to foster a spirit of nationalism and love for the country among students. These strategies are integrated into both the academic and extracurricular activities of the school. Contribution: This study contributes valuable insights for educators, policymakers, and curriculum developers on practical and culturally relevant methods to reinforce character education, particularly in cultivating national pride and patriotic values among elementary school students in Indonesia.